Whether children aged 10-12 react to FOP nutri score labels on the children’s snack packaging during the period of purchase in China / Guo Junjie, Nur Hisham Ibrahim and Muhamad Abdul Aziz Ab Gani - Junjie, Guo; Ibrahim, Nur Hisham; Ab Gani, Muhamad Abdul Aziz (Universiti Teknologi MARA, Perak, 2024)
Numerous studies have found that there are many visual design elements on children's food packaging that influence children's tasty, including color, shape, font, size, material, and brand. In recent years, more and more research has found that the role of labeling in food packaging cannot be ignored and is increasingly influencing purchasing behavior to some degree. In addition, there is a gradual upward trend regarding labeling for the improvement of healthy dietary intake of children. This study aims to analyze whether front of packaging (FOP) nutrition labeling on children's snack packaging has a positive effect on the purchasing behavior in China.